The medical observer in American football: a survey of use and efficacy. (2nd July 2020) - Kent, Jeremy B.; Wood, Colton L.; Pugh, Kelli; Statuta, Siobhan M.; MacKnight, John M.
ABSTRACT: Objectives: The growing concern over player safety and long-term health effects of sport-related concussion (SRC) led the Atlantic Coast Conference (ACC) to implement the medical observer, whose primary job is to identify SRCs not seen by sideline medical staff. The primary aim of this survey was to determine if the MO identifies SRCs the sideline medical staff missed during gameplay. Methods: The authors distributed a 19-item questionnaire to all ACC athletic departments that assessed for SRCs or non-concussion injuries that were detected by the MO during the 2015–2016 ACC football season. Results: Nineteen MOs completed the survey accounting for coverage of 56% of the total halves played by all ACC teams. A call to the field for concerns of an SRC carried a significantly higher risk of SRC diagnosis than no call to the field (RR 400.1, CI 244.6–654.1, P < .001). Four SRCs were identified by an MO that were not seen by the sideline medical staff. Conclusions: The MO detects SRCs that are not seen by the sideline medical staff. The survey also showed many ACC teams used the MO as a secondary injury observer. Each MO should be provided with the best available tools, communication, and viewing angles.